EDA-containing fibronectin increases proliferation of embryonic stem cells - Losino, Noelia Ivana (2013)
Embryonic stem cells (ESC) need a set of specific factors to be propagated. They can also grow in conditioned medium (CM) derived from a bovine granulosa cell line BGC (BGC-CM), a medium that not only preserves their main features but also increases ESC's proliferation rate. The mitogenic properties of this medium were previously reported, ascribing this effect to an alternative spliced generated fibronectin isoform that contains the extra domain A (FN EDA +). Here, we investigated if the FN EDA+ isoform increased proliferation of mouse and human ES cells. We analyzed cell proliferation using conditioned media produced by different mouse embryonic fibroblast (MEF) lines genetically engineered to express FN constitutively including or excluding the EDA domain (FN EDA-), and in media supplemented with recombinant peptides containing or not the EDA. We found that the presence of EDA in the medium increased mouse and human ESC's proliferation rate. Here we showed for the first time that this FN isoform enhances ESC's proliferation. These findings suggest a possible conserved behavior for regulation of ES cells proliferation by this FN isoform and could contribute to improve their culturing conditions both for research and cell therapy.